Korban Cyberbullying, Siapakah? - Barus, Rehia Karenina Isabella (JURNAL SIMBOLIKA: Research and Learning in Communication Study, 2019)
Cyberbullying is a new form of bullying that is commonly experienced in the real world but with the same characteristics and effects. Cyberbullying is the behavior of using information and communication technology that aims to intimidate others repeatedly and intentionally Victims of cyberbullying are "parties who are intimidated by stronger parties repeatedly through electronic media. Bodhicitta High School is an integrated school with internet where every high school student can use the internet in teaching and learning activities. This study aims to find out who is the victim of cyberbullying and also how cyberbullying behavior is experienced by victims. This study used descriptive qualitative method. A purposive technique is used to determine the informants to be interviewed. The results of the study show that not only students who are not achievers, but also students who excel even teachers are also victims of cyberbullying. The anonymity of cyberbullying is one of the most powerful reasons for triggering cyberbullying. Victims mostly experience cyberbullying behavior in the form of flaming, harassment, and also denigration.